Effects of China's "limited entertainment order" policy on program diversity: an analysis based on panel threshold model. Issue 1 (3rd April 2019) - Cheng, Jingwei; Wu, Chen; Chi, Jianyu
ABSTRACT: "Competitive duplication" is widespread in China's broadcasting market due to fierce competition. To address this issue, the National Radio and Television Administration instituted the "Limited Entertainment Order" (LEO) in 2011 with the purpose of increasing the diversity of television programs. This study employs a Panel Threshold Model and data on 32 provincial TV stations between 2009 and 2014 to examine the effectiveness of the LEO on program diversity. The descriptive statistics reveal a temporary increase in program diversity immediately following implementation of the LEO, which drops quickly thereafter. The empirical findings suggest the policy has been ineffective in promoting the genres of programs offered by provincial broadcasters. In contrast, the individual fixed effects, rating share, and advertisement dependence of TV stations have significant effects on the level of program diversity.